Beneficial Shifts in the Gut Bacterial Community of Gilthead Seabream (Sparus aurata) Juveniles Supplemented with Allium-Derived Compound Propyl Propane Thiosulfonate (PTSO) - Miguel Rabelo-Ruiz; Antonio M. Newman-Portela; Juan Manuel Peralta-Sánchez; Antonio Manuel Martín-Platero; María del Mar Agraso; Laura Bermúdez; María Arántzazu Aguinaga; Alberto Baños; Mercedes Maqueda; Eva Valdivia; Manuel Martínez-Bueno (Animals, 2022)
This study analyzes the potential use of an Allium-derived compound, propyl propane thiosulfonate (PTSO), as a functional feed additive in aquaculture. Gilthead seabream (Sparus aurata) juveniles had their diet supplemented with this Allium-derived compound (150 mg/kg of PTSO) and were compared with control fish. The effects of this organosulfur compound were tested by measuring the body weight and analyzing the gut microbiota after 12 weeks. The relative abundance of potentially pathogenic Vibrio and Pseudomonas in the foregut and hindgut of supplemented fish significantly decreased, while potentially beneficial Lactobacillus increased compared to in the control fish. Shannon’s alpha diversity index significantly increased in both gut regions of fish fed with a PTSO-supplemented diet. Regarding beta diversity, significant differences between treatments only appeared in the hindgut when minority ASVs were taken into account. No differences occurred in body weight during the experiment. These results indicate that supplementing the diet with Allium-derived PTSO produced beneficial changes in the intestinal microbiota while maintaining the productive parameters of gilthead seabream juveniles.